Evaluation of pineapple byproduct at increasing levels in heavy finishing pigs feeding - Silvestre Vasconcelos, Tarcisio [UNESP]; Thomaz, Maria Cristina [UNESP]; Castelini, Fabricio Rogério [UNESP]; Versuti Arantes Alvarenga, Patrícia [UNESP]; Alves de Oliveira, Jaqueline [UNESP]; Ferreira Ramos, Géssica [UNESP]; Keith Ono, Rafael [UNESP]; Milani, Natália Cristina; dos Santos Ruiz, Urbano (Elsevier, 2020)
The purpose of this study was to evaluate the effects of dietary pineapple byproduct increasing levels on heavy finishing pigs performance, diet nutrient and energy digestibility, digesta transit time and carcass characteristics. Thirty-two barrows (77.85 ± 2.57 kg initial body weight - BW) were used in a complete block design experiment, with 4 dietary treatments, 8 replications per treatment and 1 pig per experimental unit (pen). The pigs were fed corn-soybean meal based diets with inclusions of 0, 90, 180 and 270 g pineapple byproduct/kg, from 77.85 ± 2.57 kg to 101.25 ± 4.25 kg (Phase 1) and from to 101.25 ± 4.25 kg to 126.71 ± 8.61 kg (Phase 2) BW. Diets were formulated to provide the same levels of standardized ileal digestible lysine (8.29 and 7.48 g/kg), methionine + cysteine (4.97 and 4.21 g/kg), threonine (5.55 and 5.01 g/kg), tryptophan (1.49 and 1.35 g/kg), calcium (5.12 and 4.74 g/kg), and standardized total tract digestible phosphorous (2.50 and 2.31 g/kg) in phases 1 and 2, respectively. The pineapple byproduct sample presented (dry matter basis) 65.1 g crude protein /kg, 728.8 g total dietary fiber/kg, 49.7 g soluble dietary fiber/kg, 679.1 g insoluble dietary fiber/kg, 736 g neutral detergent fiber/kg, 318 g acid detergent fiber/kg and 17.7 MJ GE/kg. The pigs were fed ad libitum and at end of the trial were slaughtered by electrical stunning followed by exsanguination in a commercial slaughterhouse. Increasing dietary pineapple byproduct inclusion linearly decreased (P < 0.05) average daily gain (ADG - 17%–24%) and average daily feed intake (ADFI – 12–21%) in phases 1, 2 and in the overall period. Conversely, no effects (P > 0.05) were observed on feed conversion ratio. Linear decreases (P < 0.01) were observed on pre-slaughter weight, hot carcass weight, carcass yield, fat area (20 %), fat to meat ratio (22 %), backfat thickness (40 %) and lean meat amount of the pigs as a result of the increasing levels of the feedstuff. Carcass length, loin eye area, loin depth and digesta transit time were not affected (P> 0.05) by experimental diets. Increasing pineapple byproduct content in the diets linearly increased (P < 0.05) insoluble and total dietary fiber digestibility in both phases and lean meat percentage. The soluble dietary fiber digestibility and average backfat thickness showed a quadratic effect (P < 005). Increasing dietary pineapple byproduct inclusion decreased (P < 0.05) dry matter, organic matter, and energy digestibilities in phases 1 and 2, and crude protein digestibility in phase 1. Increasing levels of pineapple byproduct in the diets decreased pigs growth performance, but reduced carcass fat deposition in pigs.
Keywords: Agro-industrial waste; By-product; Carcass quality; Fat; Fiber